2005
DOI: 10.1590/s1517-83822005000300011
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of arbuscular mycorrhizal fungi in plants of Theobroma grandiflorum Schum and Paullinia cupana Mart. of aN agroforestry system in Central Amazonia, Amazonas State, Brazil

Abstract: The seasonal dynamics of Arbuscular Mycorrhizal Fungi (AMF) was investigated in the rhizosphere of two fruit species in a terra firme (upland) ecosystem in Central Amazonia. Two host species (Theobroma grandiflorum and Paullinia cupana) and nine sampling months (August, September and December/1998, February, April, May and December/1999, February and May/2000 were studied in a completely randomized design, with five replications, set in a 2 x 9 factorial experiment. Soil (0-20 cm depth) and root samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 43 publications
3
8
1
6
Order By: Relevance
“…The positive correlation between the precipitation and AMF variables in the present study were opposite to the previous finding that mycorrhizal variables and rainfall had a negative correlation (Muthukumar and Udaiyan, 2002), but consisted with other studies (Braunberger et al, 1994;Lingfei et al, 2005). Soil moisture has been reported to be positively correlated with AMF colonization (He et al, 2002;Bohrer et al, 2004;Lingfei et al, 2005, Oliveira andOliveira, 2005), which might be a strong argument supporting the present results, as precipitation is an important element of soil moisture. Negative correlations between the evaporation and AMF variables also reinforced these data.…”
Section: Discussioncontrasting
confidence: 98%
“…The positive correlation between the precipitation and AMF variables in the present study were opposite to the previous finding that mycorrhizal variables and rainfall had a negative correlation (Muthukumar and Udaiyan, 2002), but consisted with other studies (Braunberger et al, 1994;Lingfei et al, 2005). Soil moisture has been reported to be positively correlated with AMF colonization (He et al, 2002;Bohrer et al, 2004;Lingfei et al, 2005, Oliveira andOliveira, 2005), which might be a strong argument supporting the present results, as precipitation is an important element of soil moisture. Negative correlations between the evaporation and AMF variables also reinforced these data.…”
Section: Discussioncontrasting
confidence: 98%
“…Both authors suggested that AMF colonization might be influenced by environmental data, soil chemical composition and variability of the site, in addition to root architecture, inoculum potential and seasonal variation. This variation in AMF root colonization according to sites was previously reported by some authors in different ecosystems such as Alpine prairies (Ruotsalainen et al, 2002), sand dunes in arid areas (Jaiti et al, 2007;Bouamri et al, 2014) and Amazonian agroforestry system (Oliveira and Oliveira, 2005). Interestingly, our results demonstrated that combination of soil parameters and seasonal variation has significant effects on mycorrhizal root colonization.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the results of this investigation give some support to a strong influence of edaphic factors, such as pH on symbiotic association in the acid soils and nutrient-limited soils of the Western Ghat region of Goa. The present study was carried out in the dry season and it is suggested that the duration of moisture availability determines the level of AMF colonization which especially leads to improvement of soil fertility, especially the increase of pH and provides favorable environment for mycorrhizal formation and function (de Oliveira & de Oliveira, 2005). In absence of these conditions, the pH is acidic and limits the AM fungal formation.…”
Section: Discussionmentioning
confidence: 97%